2013
DOI: 10.1155/2013/647107
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of Bone Marrow-Derived Mesenchymal Stem Cells Promotes Delayed Wound Healing in Diabetic Rats

Abstract: In this paper, we established a delayed wound healing model on diabetic rat to mimic the pathophysiology of clinical patients who suffered from diabetic foot ulcers. We also evaluated if transplantation of allogeneic bone marrow-derived mesenchymal stem cells could promote the delayed wound healing and investigated the possible underlying biological mechanisms and stem cell behavior involved in this process. The results showed that bone marrow-derived mesenchymal stem cells had a positive effect on delayed wou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 44 publications
(41 reference statements)
5
53
0
2
Order By: Relevance
“…However, the host cells must be able to migrate and remodel their surroundings for the wound dressing to be effective. Thus the gel degradation rate should be kept within 40–50% over the course of 7 days [34]. …”
Section: Discussionmentioning
confidence: 99%
“…However, the host cells must be able to migrate and remodel their surroundings for the wound dressing to be effective. Thus the gel degradation rate should be kept within 40–50% over the course of 7 days [34]. …”
Section: Discussionmentioning
confidence: 99%
“…In diabetic animal models, systemic or local injections, for example, of both MSCs promote angiogenesis and migration, and they have the ability to induce regeneration rather than fi brosis in the wound microenvironment. [94][95][96] . In human diabetic foot ulcers, implantation of autologous BM-MSCs signifi cantly improves clinical parameters such as ulcer size and pain-free walking distance [ 97 ] .…”
Section: Challenges and Perspectives In The Treatment Of Chronic Wounmentioning
confidence: 99%
“…Recent studies have outlined some successful approaches to promoting wound healing with MSCs, including autologous bone marrow-derived MSCs in fibrin matrix 52 or, more recently, intramuscular injection of autologous MSCs to improve diabetic wound closure. 54 While some trials have been aimed primarily at safety of MSC use for wound healing, 50 several clinical trials have shown the potential benefit of MSCs for inclusion in wound healing devices, including improved average rate of wound healing and general limb perfusion after treatment 53 and also improved acute wound healing correlating to the number of injected cells. 52 Despite any effects on healing, there was some doubt as to any reduction in limb amputation rate or relative pain levels among groups, a major consideration for effective therapy in chronic wounds.…”
Section: Chronic Skin Woundsmentioning
confidence: 99%